Strategi Pemasaran Syariah dalam Menghadapi Persaingan Bisnis pada Syarah Bakery Kota Bengkulu - Rahmawati, Gusti; Hak, Nurul; Shar, Aan (Ekonomis: Journal of Economics and Business, 2024)
In order to cope with business competitiveness at Syarah Bakery in Bengkulu city, this research set out to identify the best marketing approach. Qualitative and quantitative descriptive research methods are used. 20 respondents were given questionnaires to complete and observations, interviews, and secondary data sources were used as the data gathering methods. The data analysis technique used is SWOT analysis. The results of the study show that the company is in the growth quadrant I, where IFAS has a score of 3.69 and EFAS has a score of 3.2. Syarah Bakery has product advantages, namely processed durian specialists, has a complete variety of products, lots of toppings in the product, products are always fresh, uses social media in promotions, such as Instagram, Facebook, and Tik-tok, has friendly employees, fast and neat in serving customers. Thus the marketing strategy implemented at Syarah Bakery is an aggressive strategy by maintaining and improving product quality, following technological advances, increasing the completeness of various product variations by participating in every existing culinary event, improving the quality of service to consumers.